2019
DOI: 10.1111/hsc.12875
|View full text |Cite
|
Sign up to set email alerts
|

What predicts the quality of life in Turkey: The results of a country representative study

Abstract: Quality of life is a multidimensional, sophisticated, comprehensive and abstract concept that reflects life conditions, health and social welfare status, perception of life and psychology of individuals. It is affected by health problem and disease existence as well as individual, demographic, economic and social characteristics such as gender, education, marital status and income level. The objective of this study is to determine the more likely predictors of the quality of life in Turkey. 2016 Turkey Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…Our study found a negative correlation between older age and lower HRQOL. This concurs with a previously conducted study ( 4 , 44 ). In addition, our study found that while more than half of respondents had enough money to buy necessities, 12.1% faced financial constraints limiting them from purchasing basic needs.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our study found a negative correlation between older age and lower HRQOL. This concurs with a previously conducted study ( 4 , 44 ). In addition, our study found that while more than half of respondents had enough money to buy necessities, 12.1% faced financial constraints limiting them from purchasing basic needs.…”
Section: Discussionsupporting
confidence: 94%
“…Then, it was piloted with 47 individuals to conduct the reliability analysis to obtain Cronbach’s alpha value. Four items were used in which participants indicated the frequency of ( 1 ) knowledge in finding opportunities to improve knowledge/education, ( 2 ) knowledge of assistance from the government to improve education and training, ( 3 ) knowledge in seeking educational opportunities and assistance from agencies other than government (e.g., NGOs & Industry), and ( 4 ) know what educational facilities to improve skills provided by the government. Using a 4-point rating scale (1 = Strongly disagree to 4 = Strongly agree), participants indicated the frequency of each item.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also impact overall health perception and life satisfaction of the patients, and act as a barrier to their health‐promoting behaviors, such as following a healthy diet or exercising regularly, and thus lead to deterioration of their well‐being and quality of life (Brod et al, 2015; Gok Metin & Arslan, 2018; Gore et al, 2005). Quality of life is a multidimensional concept, defined as the effect of health on an individual's physical, mental, and social well‐being as well as their perceived ability to function (Yetim & Celik, 2019).…”
mentioning
confidence: 99%
“…Öğrencilerin akademik hayatlarındaki başarıları da yaşam memnuniyeti üzerinde önemli bir (García-Martínez ve diğ., 2021). Diğer taraftan çocukların sosyo-ekonomik düzeyleri, yaşam standartları ve buna bağlı yaşam memnuniyetleri de eğitim süreçleri üzerinde doğrudan ve dolaylı etkiler oluşturmaktadır (Yetim ve Çelik, 2019). Akademik alanda başarılı olan gençler, sahip oldukları bilgi ve beceri ile karşılaştıkları meşakkatli süreçleri akranlarına göre başarılı yönetmekte ve stres ile başa çıkma çıkmak konusunda daha başarılı görünmektedirler.…”
Section: Dijital Bağımlılıklar Akademik Yılmazlık Ve Yaşam Memnuniyetiunclassified